2020
DOI: 10.1109/access.2020.3024727
|View full text |Cite
|
Sign up to set email alerts
|

Solver-Based Mixed Integer Linear Programming (MILP) Based Novel Approach for Hydroelectric Power Generation Optimization

Abstract: In Pakistan, hydroelectric power is one of the reliable sources of electricity with a capacity of 8,713 MW, which is 29% of the total energy mix. Hence, with such a vast resource capacity of hydroelectric power, its optimization and dispatch planning will have a great significance. This research work discusses the importance of hydroelectric power generation planning for both storage and run-of-river (ROR) hydropower plants, as well as; a solver-based optimization technique is proposed for the first time to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…To solve the problem by the linear programming methodology, the solver tool of the excel program was specifically used . It was solved by the simplex method as this method solves such problems (appendix 1, appendix 2) [3,19]. Data for the study area were also used for irrigation, fertilization, working hours (labor), and land use.…”
Section: Linear Programming For Crop Distribution/managementmentioning
confidence: 99%
“…To solve the problem by the linear programming methodology, the solver tool of the excel program was specifically used . It was solved by the simplex method as this method solves such problems (appendix 1, appendix 2) [3,19]. Data for the study area were also used for irrigation, fertilization, working hours (labor), and land use.…”
Section: Linear Programming For Crop Distribution/managementmentioning
confidence: 99%
“…Identifying and qualifying this behaviour is not an easy task instead they are reected back in the driver's action while driving. These actions could be recorded in the form of vehicle's /driver's kinematic data like over speeding, acceleration/deceleration, jerk, tailgating, lane change variation, etc [11]. Few researchers in their respective study have highlighted and indicated these kinematic parameters (speed, acceleration/deceleration, and jerk) to be an important parameter in identifying aggressive behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, it is proposed to use the theory of marginal utility as a basis, which, in combination with optimization models, will make it possible to develop the required methodology. With regard to our investigation, water and fuel are considered as products used for generation of the same amount of electricity [17][18][19].…”
Section: Mathematical Model For Determining the Cost Of A Hydro Resou...mentioning
confidence: 99%
“…It should be noted that when constructing the marginal cost curve for hydropower plants, restrictions on the throughput of the turbine and the power of the generator were taken into account. Further, using expression (18), we find the optimal production volumes of the Novosibirsk HPP for each season of the year. The calculation results are summarized in Table 3.…”
Section: Uvmentioning
confidence: 99%
See 1 more Smart Citation